2009
DOI: 10.1007/s10928-009-9116-x
|View full text |Cite
|
Sign up to set email alerts
|

Fractional kinetics in drug absorption and disposition processes

Abstract: We explore the use of fractional order differential equations for the analysis of datasets of various drug processes that present anomalous kinetics, i.e. kinetics that are non-exponential and are typically described by power-laws. A fractional differential equation corresponds to a differential equation with a derivative of fractional order. The fractional equivalents of the "zero-" and "first-order" processes are derived. The fractional zero-order process is a power-law while the fractional first-order proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
101
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 25 publications
1
101
0
3
Order By: Relevance
“…We can observe that all schemes met the control objective-taking all of the patients to BIS = 50. It can be seen that the controllers based on the second-order (14) and third-order models (15) had better performances than the controllers based on the first-order structure (13). Figure 10 shows the control input of the four implemented controllers and it a similar behavior can be seen between the controllers.…”
Section: Inter-patient Robustnessmentioning
confidence: 79%
See 4 more Smart Citations
“…We can observe that all schemes met the control objective-taking all of the patients to BIS = 50. It can be seen that the controllers based on the second-order (14) and third-order models (15) had better performances than the controllers based on the first-order structure (13). Figure 10 shows the control input of the four implemented controllers and it a similar behavior can be seen between the controllers.…”
Section: Inter-patient Robustnessmentioning
confidence: 79%
“…Therefore, with the identification scheme and the simulation presented, it is shown that the proposed models were able to capture the input-output behavior of the presented example. Moreover, it was shown that the simple fractional-order models (13)(14)(15) are able to capture the responses of the patients, as illustrated in Figure 4.…”
Section: Identificationmentioning
confidence: 99%
See 3 more Smart Citations